International standards and the WTO TBT Agreement: Improving governance for regulatory alignment - Erik Wijkström; Devin McDaniels (World Trade Organization (WTO), 2013)
The WTO TBT Agreement obliges governments to use international standards as a basis for regulation, yet leaves a degree of flexibility with respect to the choice of standard, and the manner of its use. This interplay between obligation and flexibility has given rise to tension in various fora of the WTO, including in committee work, negotiations and dispute settlement. This paper brings together these three distinct strands of WTO work to illustrate core aspects of the international standards debate at the WTO. In our analysis we first briefly outline the nature of the discipline in the TBT Agreement itself; next, we describe where and how the discussion arises in the WTO; and, finally, explore some implications of governance of international standard setting. We propose that greater regulatory alignment could be achieved through a renewed focus on the procedures of setting international standards (the how), and greater emphasis on robust technical/scientific underpinnings of such standards (the what).
Keywords: F13; F53; F55; K33; L15; L51; 330; international trade; international standards; international cooperation; coherence; non-tariff barriers; technical barriers to trade; regulation; WTO-Regeln; Nichttarifäre Handelshemmnisse; Welt